Linking framing analysis and international news communication: a content analysis of newspaper coverage on the Sept. 11 attacks, Bali bombing and Madrid train bombing - Tan, Joann Li Hoeng (2008)
The aim of this cross-national study is two-fold: first, to examine framing techniques by determining which news frames (e.g. threat to economy or political climate) were dominant during each attack; and second, to integrate possible factors influencing international news flow (e.g. trade volume and geographic distance) to the theory of framing analysis. Using the factors as independent variables, the data from the newspapers is submitted to regression analyses to establish the extent of the relationship between the two theories.